THE EFFECT OF INCREASING JOB TRAINING ON CIVIL SERVANT PRODUCTIVITY AT THE PROBOLINGGO SUB-DISTRICT OFFICE, EAST JAVA - Wahyu Nurhidayah, Fitriana; Husni Mubaroq; Nourma Ulva Kumala Devi (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This research is motivated by the importance of improving the quality of human resources, especially Civil Servants (PNS), in supporting effective and efficient government performance. This study aims to determine the effect of increasing job training on the work productivity of civil servants at the Patokan Village Office, Kraksaan District, Probolinggo Regency. The research method used is a quantitative method. Data collection was carried out by distributing questionnaires to respondents who were civil servants at the village office. The data analysis technique used is a simple linear regression analysis to see the relationship between job training variables and work productivity. The results of the study show that job training has a positive and significant effect on the work productivity of civil servants. This is evidenced by a significance value of less than 0.05, as well as a determination coefficient that shows that job training makes a significant contribution to increasing employee work productivity. The conclusion of this study is that the increase in job training has a direct effect on increasing the work productivity of civil servants. Therefore, it is recommended that the village office continue to develop relevant, structured, and appropriate job training programs according to the needs of employees to improve overall organizational performance.